2020
DOI: 10.1111/jiec.12999
|View full text |Cite
|
Sign up to set email alerts
|

City‐level water withdrawal in China: Accounting methodology and applications

Abstract: In the context of the freshwater crisis, accounting for water withdrawal could help planners better regulate water use in different sectors to combat water scarcity. However, the water withdrawal statistics in China are patchy, and the water data across all sectors at the city level appear to be relatively insufficient. Hence, we develop a general framework to, for the first time, estimate the water withdrawal of 58 economic-social-environmental sectors in cities in China. This methodology was applied because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
(67 reference statements)
2
19
0
Order By: Relevance
“…We applied the general accounting framework used in previous work, and built up city-level and territory-based industrial water withdrawal data for individual sector and city, according to IPCC administrative boundary (scope 1) 49 . For method validation please refer to detailed discussion in previous paper 32 and Turner et al (2010) 50 . Of 343 cities, only 272 cities' data were available for sectoral accounting datasets, and 343 were further accounted for total blue-water withdrawal, availability and quantitative blue-water scarcity status.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We applied the general accounting framework used in previous work, and built up city-level and territory-based industrial water withdrawal data for individual sector and city, according to IPCC administrative boundary (scope 1) 49 . For method validation please refer to detailed discussion in previous paper 32 and Turner et al (2010) 50 . Of 343 cities, only 272 cities' data were available for sectoral accounting datasets, and 343 were further accounted for total blue-water withdrawal, availability and quantitative blue-water scarcity status.…”
Section: Methodsmentioning
confidence: 99%
“…Industrial sectors in 272 cities were investigated for two reasons: first, there were special regulations for industrial water withdrawal intensity in the redline policy; a number of cities were even required to implement the most up-to-date technologies or regulatory standards for water savings during industrial production. Second, the 41 industrial sectors we considered in total (see appendix III details) showed high heterogeneity in water use and saving potential 32 .…”
Section: Industrial Water Saving Potential Based On Efficiency Improvementmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Meanwhile, the coal-based thermal power generation requires large volumes of water for cooling purposes in China. 4 , 5 , 6 The thermal power generation is thirsty for water, especially in the arid northwestern regions where large coal mines are located. 7 , 8 , 9 Water scarcity has become one of the important environmental constraints for deploying thermal power plants in catchments under high water stress.…”
Section: Introductionmentioning
confidence: 99%